The Influence of the Lectin Pathway of Complement Activation on Infections of the Respiratory System - Świerzko, Anna S.; Cedzyński, Maciej (Frontiers in Immunology, 2020)
Lung diseases are among the leading causes of morbidity and mortality. Complement activation may prevent a variety of respiratory infections, but on the other hand, could exacerbate tissue damage or contribute to adverse side effects. In this review, the associations of factors specific for complement activation via the lectin pathway (LP) with infections of the respiratory system, from birth to adulthood, are discussed. The most extensive data concern mannose-binding lectin (MBL) which together with other collectins (collectin-10, collectin-11) and the ficolins (ficolin-1, ficolin-2, ficolin-3) belong to pattern-recognition molecules (PRM) specific for the LP. Those PRM form complexes with MBL-associated serine proteases (MASP-1, MASP-2, MASP-3) and related non-enzymatic factors (MAp19, MAp44). Beside diseases affecting humanity for centuries like tuberculosis or neonatal pneumonia, some recently published data concerning COVID-19 are summarised.